2004
DOI: 10.1073/pnas.0405843101
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium VirB10, an ATP energy sensor required for type IV secretion

Abstract: Bacteria use type IV secretion systems (T4SS) to translocate DNA and protein substrates to target cells of phylogenetically diverse taxa. Recently, by use of an assay termed transfer DNA immunoprecipitation (TrIP), we described the translocation route for a DNA substrate [T-DNA, portion of the Ti (tumor-inducing) plasmid that is transferred to plant cells] of the Agrobacterium tumefaciens VirB͞D4 T4SS in terms of a series of temporally and spatially ordered substrate contacts with subunits of the secretion cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(178 citation statements)
references
References 39 publications
6
170
0
2
Order By: Relevance
“…The recently proposed 'shoot and pump' model suggests that the coupling protein secretes the relaxase into the conduit created by the T4SS and subsequently threads the DNA portion of the substrate through a channel that is formed by the hexameric coupling protein (Llosa & de la Cruz, 2005). Furthermore, the A. tumefaciens coupling protein, VirD4, has been found to require functional NTPbinding motifs for bridging the inner and outer subassemblies of VirB/D4 T4SS (Cascales & Christie, 2004a). Clearly, the coupling protein plays a vital role in the transfer of plasmid DNA from donor to recipient cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently proposed 'shoot and pump' model suggests that the coupling protein secretes the relaxase into the conduit created by the T4SS and subsequently threads the DNA portion of the substrate through a channel that is formed by the hexameric coupling protein (Llosa & de la Cruz, 2005). Furthermore, the A. tumefaciens coupling protein, VirD4, has been found to require functional NTPbinding motifs for bridging the inner and outer subassemblies of VirB/D4 T4SS (Cascales & Christie, 2004a). Clearly, the coupling protein plays a vital role in the transfer of plasmid DNA from donor to recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…The coupling proteins TraG and TrwB from the R27 and R388 plasmids, respectively, were both independently determined to interact with the VirB10-like proteins, TrhB and TrwE, from R27 and R388 (Gilmour et al, 2003;Llosa et al, 2003). In the Ti plasmid of Agrobacterium tumefaciens, VirB10 is a well-conserved T4SS component and it has been recently proposed to be the ATP energy sensor of the T4SS (Cascales & Christie, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Protease susceptibility experiments have shown that VirB10 can adopt two diVerent conformations, one of which requiring the presence of cellular ATP (Cascales and Christie, 2004a). Closer inspection has revealed that it is the ATP utilization by VirB11 and VirD4 (but not VirB4) that is responsible for the switch from the ATP-independent to the ATP-dependent "energized" conformation of VirB10 (Cascales and Christie, 2004a).…”
Section: Virb10: An Energy Sensor Gating the Mpf Channelmentioning
confidence: 99%
“…Closer inspection has revealed that it is the ATP utilization by VirB11 and VirD4 (but not VirB4) that is responsible for the switch from the ATP-independent to the ATP-dependent "energized" conformation of VirB10 (Cascales and Christie, 2004a). Only the energized conformation of VirB10 is able to form complexes with the outer-membrane component VirB9.…”
Section: Virb10: An Energy Sensor Gating the Mpf Channelmentioning
confidence: 99%
“…VirB10 is essential for the transfer of the substrate from the inner to the outer membrane but does not directly contact the substrate (16). Instead, it acts as an energy-sensing bridge between the inner and outer membranes (17). Interactions between VirB8 and many other T4SS proteins have been reported, including VirB10 (18,19), VirB9 (19), VirB1, VirB4, and VirB11 (20), as well as with itself (18)(19)(20).…”
mentioning
confidence: 99%